The movement control order (MCO) for Covid-19 crisis and its impact on tourism and hospitality sector in Malaysia - Karim, Wasiul; Haque, Ahasanul; Anis, Zohurul; Ulfy, Mohammad Arije (Research Publishing Academy ( RPA), 2020)
The recent outbreak of Novel Coronavirus COVID-19 has led to a global panic due to its fatal nature. Malaysia is currently being aware of this pandemic disease and the government has imposed Movement Control Order (MCO) for preventing the spread of this disease. The ongoing Visit Malaysia 2020 campaign has been cancelled and all the guests who are currently staying in Malaysia have been told to remain in their room during the MCO. Therefore, the aim of this study is to examine the future impact of tourism and hospitality industry due to restricted movement control order for novel COVID-19. The conceptual methodology technique is used for this study to imply secondary information from various government published sources. The major findings are indicated about the flight operations as minimized and employees from different hotels as well as resorts were asked for unpaid leave. Moreover, results is also highlighted about negatively impact on Malaysian tourism and hospitality industry due to seriously pandemic disease spreading worldwide. Although, this sector is considered as the world's fastest-growing economy. In conclusion, this conceptual study will further help the authority to take precautions and best policy to be implemented in future.